The Job Creation Act: Implication of National Strategic Project on Regional Spatial Planning (Study in Madiun City, East Java Province) - Riska Purbasari; Mohammad Jamin (Muhammadiyah University Press, 2021)
Purpose of the study: This study aims to examine the implications of implementing the National Strategic Project for regional spatial planning, especially Madiun city, after the enactment of Act Number 11 of 2020 on Job Creation.Methodology: This study is normative legal research using a statute and conceptual approaches. The research was conducted by analyzing laws and regulations as primary legal materials and expert notions/doctrine and literature studies as secondary legal materials.Results: The study results indicate that the implementation of the National Strategic Project after the enactment of Act Number 11 of 2020 on Job Creation has implications for the existence of agricultural land, environment, economic, and social aspects in Madiun City.Applications of this study: This study is expected as a consideration for the Central Government in reviewing and formulating national strategic policies that affect spatial planning in the regions. For city/district governments, this study can be used as a contribution of thought to determine the steps that need to be taken in implementing National Strategic Projects in their regions.Novelty/Originality of this study: This research has a novelty by examining the laws and national strategic policies that the government has just released in recent years. The similarity of regional characteristics between Madiun City and many cities/districts that implement the National Strategic Project can provide an overview of the implications faced by the regions.